Structural, electronic, and magnetic properties of CoFeVGe-based compounds: Experiment and theory - Parashu Kharel; Zachary Lehmann; Gavin Baker; Lukas Stuelke; Shah Valloppilly; Paul M. Shand; Pavel V. Lukashev (AIP Advances, 2023)
We have carried out a combined theoretical and experimental investigation of both stoichiometric and nonstoichiometric CoFeVGe alloys. In particular, we have investigated CoFeVGe, Co1.25Fe0.75VGe, Co0.75Fe1.25VGe, and CoFe0.75VGe bulk alloys. Our first principles calculations suggest that all four alloys show ferromagnetic order, where CoFeVGe, Co1.25Fe0.75VGe, and Co0.75Fe1.25VGe are highly spin polarized with spin polarization values of over 80%. However, the spin polarization value of CoFe0.75VGe is only about 60%. We have synthesized all four samples using arc melting and high-vacuum annealing at 600 °C for 48 hours. The room temperature x-ray diffraction of these samples exhibits a cubic crystal structure with disorder. All the samples show single magnetic transitions at their Curie temperatures, where the Curie temperature and high field (3T) magnetization are 288 K and 42 emu/g; 305 K and 1.5 emu/g; 238 K and 39 emu/g; and 306 K and 35 emu/g for CoFeVGe, Co1.25Fe0.75VGe, Co0.75Fe1.25VGe, and CoFe0.75VGe, respectively.